EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA PAPAN FLANEL PADA PERSAMAAN GARIS LURUS DI SMP - Santikarani, Otih; Yusmin, Edy; T, Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is an experimental study using pre-Experimental with One Group Posttest design which aims to find the effectiveness of Discovery Learning assisted by flannel board media on a straight-line equation in SMP Negeri 20 Pontianak. The population in this study was the students of grade VIII.The samples were taken from the students of class VIII F selected by using purposive sampling techniques. The data collection technique used the test, observation sheets and questionnaires. The test used is the achievement test. The test results of student learning that the percentage of classical mastery learning is 82% with a value ≥75. Observation sheet is observed process and learning activities of students. Acquisition of learning process an average is 3.61 with very good category. Observation of student learning activities amounted to 88.68% with very good category. The student questionnaire responses is 78% with a positive category. It can be concluded that learning with Discovery Learning model assisted by flannel board media is effective.Keywords: Effectiveness, Discovery Learning Model, Board Flannel Media, Straight Line Equation